Особенности гнездования шилоклювки в районе Черноморского заповедника - Ардамацкая, Т.Б. (Вестник зоологии, 1982)
Theavocet nestingin the Black Sea naturereserveundergoes specific habitat con- ditions. Egg size depends on different nesting sites. Colony size varies from 3 to 252 nests, many colonies are mixed. Average clutch number essentially differs in different habitats and within a habitat from year to year. Egg size in normal clutches is larger than ni repeated.Natural egg mortality is negligibly low. Under the absence of November temperature fall, last birds rest until 17-28 November.